Analyzing a faculty online learning community as a mechanism for supporting faculty implementation of a guided-inquiry curriculum - Edward Price; Alexandra C. Lau; Fred Goldberg; Chandra Turpen; P. Sean Smith; Melissa Dancy; Steve Robinson (SpringerOpen, 2021)
Abstract Background Adoption and use of effective, research-based instructional strategies (RBISs) for STEM education is less widespread than hoped. To promote further use of RBISs, the propagation paradigm suggests that developers work with potential adopters during the development process, and provide ongoing support after adoption. This article investigates the impact of a faculty online learning community (FOLC) as a professional development mechanism for supporting faculty adopting a research-based curriculum. A FOLC uses video conference technology and online platforms to connect geographically dispersed faculty with similar backgrounds (e.g., physics faculty) and supports their teaching development. In the context of a specific FOLC, this article seeks to determine the outcomes the FOLC achieves, and how. Results Analysis of a FOLC meeting identified opportunities for rich, complex social interaction centered on the research-based curriculum. By functioning as a sounding board for ideas, a space to share experiences, a source of affective support, and a venue for troubleshooting, the FOLC mediates the achievement of a range of outcomes related to implementation of the curriculum. Survey results indicate that members feel a sense of community in the FOLC and that it provides encouragement through teaching challenges. Further results indicate participants' increased confidence in using the curriculum; familiarity with the curriculum structure and content; increased knowledge of pedagogical techniques; reflection on teaching practices in the curriculum; and use of pedagogical techniques aligned with the curriculum's core principles. Emerging evidence supports more distal outcomes, including student learning, persistence in using the curriculum, reflection in teaching practice across courses taught, and use of research-based pedagogy in other courses. Conclusions The propagation paradigm emphasizes the need for ongoing support for adopters of RBISs. The FOLC model provides participating faculty with ongoing support through participation in a community and is an effective support mechanism for adopters of a research-based curriculum. In this study, FOLC members are increasing their knowledge and use of pedagogical techniques in the curriculum-specific course and beyond. This is facilitated by the opportunities in the FOLC for troubleshooting, idea sharing, and receiving encouragement through challenges. This model has the potential to support adopters of additional educational innovations.